Creating a Thermal Burn Wound Model in Rabbits for Application in Wound Treatment - Dung, Ho My; Thi Thom, Vu; Thi Thuy An, Pham; Hong Minh, Phan; Thi Phuong, Ta; Hong Duc, Vu; Quynh Anh, Dang; Nhat Long, Do; Thi Quynh, Do (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 2, 2025)
Currently, burn injuries have become a concerning issue in many countries, affecting everyone at different ages and occupations. This study aimed to create a heat burn model in rabbits to optimize burn procedures, which is a premise for developing new treatment methods for burn wounds in preclinical and clinical practices. Healthy white New Zealand male rabbits were maintained in the appropriate living conditions and diet for 7 days before the experiment. The rabbits were anesthetized with chloral hydrate at 150 mg/kg via the ear vein. A metal block (200g in weight, 3cm in diameter) heated by boiling water to 100 °C was used to cause 4 burn wounds on the shaved skin of the rabbit's back, with exposure times of 10 seconds, 20 seconds, and 30 seconds. The wound healing process was monitored, and histopathological analysis at the burn site was evaluated on the 7 th and 14 th days. The results indicated that the exposure times of 10 and 20 seconds caused second-degree burns (damage to the dermis layer), while that of 30 seconds caused third-degree burns (damage to the hypodermis layer). Thus, the research successfully created a burn model on rabbit skin, laying the groundwork for future testing phases of new burn treatment methods.